Revolutionizing Inventory Management: Web-Based System for Accurate and Efficient Reporting: Merevolusi Manajemen Inventaris: Sistem Berbasis Web untuk Pelaporan yang Akurat dan Efisien - Triwahono, Handi; Rosid, Mochamad Alfan; Setiawan, Hamzah; Hindarto, Hindarto (Indonesian Journal of Innovation Studies, 2023)
The aim of this research is to develop a systematic information system for logistics of consumable goods by applying the FIFO method. It also aims to synchronize expenditure reports with inventory reports to minimize discrepancies between financial and inventory reports. The research approach consists of two methods, qualitative case study and FIFO inventory management method. The Web-based Consumable Goods Logistics Information System is built using PHP version 8.1 programming language with Laravel version 9 framework on the server-side, Vue.js on the client-side, and MySql as the database. It can be operated on browsers such as Chrome, Mozilla Firefox, or Microsoft Edge. The system is expected to help local governments generate the required reports for the BPKAD, which mandates monthly inventory reports on incoming and outgoing goods. The application is user-friendly and capable of producing accurate and fast reports. Highlights: 1. This research aims to create a systematic information system for consumable goods logistics using the FIFO method to minimize discrepancies between financial and inventory reports. 2. The Web-based system is user-friendly, capable of producing accurate and fast reports, and fulfills the inventory reporting needs of each department/unit while providing valid data to the Health Department. 3. The system is built using PHP 8.1 and Laravel 9 framework on the server-side, Vue.js on the client-side, and MySql as the database, and can be operated on Chrome, Mozilla Firefox, or Microsoft Edge browsers.